A First Principle Calculation of Full-Heusler Alloy Co2TiAl: LSDA+U Method. (16th August 2012) - Rai, D. P.; Thapa, R. K.
Abstract : We performed the structure optimization of Co2 TiAl based on the generalized gradient approximation (GGA) and linearized augmented plane wave (LAPW) method. The calculation of electronic structure was based on the full-potential linear augmented plane wave (FP-LAPW) method and local spin density approximation exchange correlation LSDA+U . We also studied the impact of the Hubbard potential or onsite Coulomb repulsion (U ) on electronic structure; the values are varied within reasonable limits to study the resulting effect on the physical properties of Co2 TiAl system. The calculated density of states (DOS) shows that half-metallicity of Co2 TiAl decreases with the increase in U values.